B-Frames: Efficiency Analysis for Digital Video Tampering Detection in Videos with Variable GOP Structure - Joshi, V; Jain, S; Bansal, C (International Journal of Computer Sciences and Engineering, 2025)
Digital video tampering is an act of malicious modification of video content. This could be done to hide or cover an object or to alter the meaning conveyed by the digital video. The research performed is summarized in this paper by analyzing various inter frame forgery detection approaches for digital video, proposed so far, highlighting the strengths and weaknesses of each approach discussed. All approaches proposed so far are making use of P-frames for forgery detection. Comparison of P-frames and B-frames has been performed in terms of complexity and accuracy of algorithms developed using each of them. All the way through the research performed, authors tried to access the worth of B-frames in digital video forgery detection.